Child and adolescent maltreatment patterns and risk of eating disorder behaviors developing in young adulthood. (October 2021) - Ziobrowski, Hannah N.; Buka, Stephen L.; Austin, S. Bryn; Duncan, Alexis E.; Simone, Melissa; Sullivan, Adam J.; Horton, Nicholas J.; Field, Alison E.
Abstract: Background: Child maltreatment may be an important risk factor for eating disorder (ED) behaviors. However, most previous research has been limited to clinical, female, and cross-sectional samples, and has not adequately accounted for complex abuse patterns. Objective: To determine whether women and men with distinct patterns of child and adolescent maltreatment have higher risks of developing ED behaviors in young adulthood than individuals with a low probability of maltreatment. Participants and setting: Data came from 7010 U.S. women and men (95% White) in the Growing Up Today Study, a prospective, community-based cohort study (14 waves between 1996 and 2016). Methods: We used a previously created maltreatment variable that was empirically derived using latent class analysis. Maltreatment groups were characterized as: "no/low abuse, " "child physical abuse, " "adolescent emotional abuse, " "child and adolescent physical and emotional abuse, " and "child and adolescent sexual abuse." We estimated risk ratios for ED behaviors developing in young adulthood using the modified Poisson approach with generalized estimating equations. We stratified models by sex. Results: Groups characterized by maltreatment had elevated risks of incident ED behaviors compared with the "no/low abuse" group among both women and men. For women, risks tended to be strongest among the "child and adolescent sexual abuse" group. For men, risks tended to be strongest among the "child and adolescent physical and emotional abuse" group. Risks were particularly strong for purging behaviors. Conclusion: Risk of incident ED behaviors in young adulthood varied by distinct maltreatment groups. Detecting maltreatment early may help prevent EDs and subsequent maltreatment.